2001
DOI: 10.1007/s002040100276
|View full text |Cite
|
Sign up to set email alerts
|

Tissue concentrations and induction of a hepatic monooxygenase in male Wistar rats after repeated doses of defined polychlorinated dibenzo-p-dioxin and dibenzofuran (PCDDs and PCDFs) mixtures

Abstract: Two groups of male Wistar rats were treated 16 times (every 3rd day) subcutaneously with a defined mixture of polychlorinated dibenzo-p-dioxins (PCDDs) or of polychlorinated dibenzofurans (PCDFs). These mixtures contained no measurable amount of 2,3,7,8-TCDD. Each single dose was calculated to contain either 57 ng I-TEq (international 2,3,7,8-T4CDD toxicity equivalencies)/kg body weight of the PCDD mixture or 39 ng I-TEq/kg body weight of the PCDF mixture. Both mixtures contained a large excess of non-2,3,7,8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…This has been shown for PCDDs in animal studies (Korner et al, 2002), and can be assumed for the Spanish families, unless all components of the mixture were eliminated from the adipose tissue at an extremely slow rate. A change in the composition of the body burdens is shown by the ratios between various components (Table 3).…”
Section: Ratio Of Different Pcdds Over a Period Of 6 Yearsmentioning
confidence: 87%
“…This has been shown for PCDDs in animal studies (Korner et al, 2002), and can be assumed for the Spanish families, unless all components of the mixture were eliminated from the adipose tissue at an extremely slow rate. A change in the composition of the body burdens is shown by the ratios between various components (Table 3).…”
Section: Ratio Of Different Pcdds Over a Period Of 6 Yearsmentioning
confidence: 87%
“…On the other hand, Nagao et al (1993) showed that the TEF of 0.5 for 4-PeCDF, proposed already by NATO/CCMS (1988a) and retained for mammals and fish by WHO in 1998, overestimated the cleft palate inducing potency of 4-PeCDF in mice about 2.5-fold, suggesting 0.2 as a TEF; the potencies of the PCDF mixtures studied were also clearly overestimated, unlike those of the PCDD mixtures that better conformed with WHO TEFs. Korner et al (2002) concluded that I-TEFs overestimated the potency for EROD induction of the mixtures including 4-PeCDF in the concentration range tested in rats. It thus is possible that the risks associated with 4-PeDCF differ from those indicated by the present TEFs.…”
Section: Risk and Uncertainty Characterizationmentioning
confidence: 94%
“…There is less information on the pharmacokinetics of other DLCs than TCDD, including PCBs, and on mixtures of DLCs especially in chronic exposures , Krowke et al 1990, Darnerud et al 1996b, Kodavanti et al 1998, van der Plas et al 1998, Korner et al 2002. The total effect of congener-specific kinetics is thus difficult to elucidate.…”
Section: Absorption Distribution Metabolism and Excretionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, weaker PCB congeners displayed response curves that were displaced to the right of the TCDD response curve to a much greater extent than would be predicted by current TEF estimates. For example, the ratio of EROD (Korner et al, 2002). In this study, animals were repeatedly treated with a I-TEq-(international 2,3,7,8-TCDD toxicity equivalencies) defined mixture of PCDDs in a comparison to TCDD.…”
Section: Uncertain Ability Of Rat Models To Predict Human Sensitivitymentioning
confidence: 99%